Indication of the Present Tense in Surah (Al-zumar):A Study of Its Meaning - Karim Salem, Mona Saadi (Journal of Tikrit University for Humanities, 2024)
The research discusses the importance of the verb and its role in revealing the meaning of Quranic texts, leading to an understanding of the meanings and contents of these texts by deriving the temporal implications of verbs, specifically the present tense, in Surah (Az-Zumar). This is due to the frequent occurrences and the diverse temporal connotations of these verbs, influenced by both linguistic and contextual indicators.